2014
DOI: 10.3748/wjg.v20.i29.10128
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity support or weight loss counseling for nonalcoholic fatty liver disease?

Abstract: Intensive psychological counseling for PA produces hepatic effects not different from standard CBT, improving physical fitness and liver fat independent of weight loss. Strategies promoting exercise are worth and effective in motivated patients, particularly in lean NAFLD patients where large weight loss cannot be systematically pursued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Considering the reduction observed for the NAFLD grade, this result was expected, as NAFLD worsens the state of IR and may lead on to type 2 diabetes in the predisposed subjects[48]. Improvement of IR was expected considering that it was already observed in previous studies as a consequence of treatment centered either on MedDiet[46] or increased physical activity[37]. …”
Section: Discussionmentioning
confidence: 87%
“…Considering the reduction observed for the NAFLD grade, this result was expected, as NAFLD worsens the state of IR and may lead on to type 2 diabetes in the predisposed subjects[48]. Improvement of IR was expected considering that it was already observed in previous studies as a consequence of treatment centered either on MedDiet[46] or increased physical activity[37]. …”
Section: Discussionmentioning
confidence: 87%
“…He concluded that lifestyle modifications that led to weight reduction and/or increased physical activity greatly reduced liver fat and improved insulin sensitivity. More recently a study led by Montesi et al [47] found that intensive psychological counseling for physical activity improves physical fitness and liver fat independent of weight loss. Similar effects have been also verified by a recent meta-analysis study [48] .…”
Section: Dietary Modifications and Exercisementioning
confidence: 99%
“…The type of weight loss with a traditional low fat diet or calorie restriction is still debatable. All of these studies though, have particularly in lean NAFLD patients where large weight loss cannot be systematically pursued [47,65] .…”
Section: Dietary Modifications and Exercisementioning
confidence: 99%
“…While exercise improves hepatic steatosis and underlying metabolic abnormalities in NAFLD, more studies are needed to define the most beneficial form and duration of exercise treatment [112,113]. Exercise should be promoted in motivated individuals, particularly in lean NAFLD patients where large weight loss cannot be pursued [114]. An experimental study in mice has also shown that regular exercise may protect from HCC development and this could be a further rationale for promoting regular PA in human NASH [115].…”
mentioning
confidence: 94%